The influence of warming, site characteristics, and host plant on root-associated fungal communities from Alexandra Fiord in the Canadian High Arctic. - Fujimura, Kei E. (Author); Egger, Keith (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2006)
No abstract available. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1302871